Uji Efek Teratogen Ekstrak Etanol Daun Patikan Kebo (Euphorbia Hirta L.) Terhadap Fetus Mencit Putih - Suhatri Suhatri; Agusdi Firdaus; Zet Rizal (STIFARM Padang, 2014)
Has done research about the teratogenic effects ethanol of extract test patikan Kebo leaves (Euphorbia hirta L.) concerning to fetal white mice. Animal experiments were grouped into 4 groups consisting of group I as negative control given only 0.5% suspension of Na CMC, group II, group III and group IV was given the ethanol extract of patikan kebo leaves with variations dose of 25 mg / kg BW, 50 mg / kg BW, and 100 mg / kg BW once a day from day 6 to day 15 of pregnancy. 18th day of pregnancy mice dilaparaktomi. Dose of 25 mg / kg BW, dose of 50 mg / kg BW did not cause teratogenic effects. Teratogenic effect was found at dose of 100 mg/kg BW there was the discovery of defects cleft palate. The results showed the ethanol extract of patikan kebo leaves not affected weight gain parent mice were significantly (p> 0.05) when compared to the negative control. Amount of fetuses were significantly reduced (p <0.05) when compared to the negative control. Fetal weight showed no significant effect (p> 0.05) if compared with negative controls.